Deshaciendo los nudos del tiempo: tres hipótesis sobre el origen y las transformaciones del calendario mexica (1403-1507) - Gabriel K. Kruell (Journal de la Société des Américanistes, 2021)
Calendars are time-quipping tools that have a history of their own, marked by an origin and eventually by its disappearance, and which are subject to changes during their lifetime that modify some aspects of their operations and structure. In this article, we want to show that the Mexica calendar, which was part of the wide and varied group of Mesoamerican calendars, was not exempt from these historical vicissitudes. Through a reverse procedure, the calendrical transformations operated by Moctezuma II in 1507 and the two adjustments of the Mexica year to the length of the tropic year made perhaps in 1507 and 1455 will be revealed. At the end, a possible date of origin of the Mexica calendar date will be proposed and will be placed at the beginning of the 15th-century, a period in which the city of Tenochtitlan was subject to Azcapotzalco, and was ruled by its first ruler Acamapichtli or maybe by his son Huitzilihuitl.